Poison ivy : how elite colleges divide us - Mandery, Evan J. (New York : The New Press, 2022)
"An eye-opening look at how America's elite colleges and suburbs help keep the rich rich--making it harder than ever to fight the inequality dividing us today"--
Going up -- Falling off -- The top floor and the iron ceiling -- Finding the escalator -- Cracking the code -- Green fences-the games kids play -- The well-rounded man -- Affirmative action for rich whites -- Doing good -- The best and the brightest-building the meritocracy myth -- The doubly disadvantaged -- Learning to party -- How liberals become conservative -- Still separate, still unequal -- How Michael Lewis ruined baseball -- You say you want a revolution -- Making college pay -- We need you, Mr. Grassley -- One percent solutions -- Communities of opportunity -- Postscript: With privilege goes responsibility.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Universities and colleges -- United States -- Admission; Education, Higher -- Social aspects -- United States; Education, Higher -- Economic aspects -- United States; Elite (Social sciences) -- United States; Income distribution -- United States; Universités -- États-Unis -- Admission; Enseignement supérieur -- Aspect social -- États-Unis.; Enseignement supérieur -- Aspect économique -- États-Unis.; Élite (Sciences sociales) -- États-Unis.; Revenu -- Répartition -- États-Unis.; EDUCATION / General; Education, Higher -- Economic aspects; Education, Higher -- Social aspects; Elite (Social sciences); Income distribution; Universities and colleges -- Admission; United States; EDUCATION / Schools / Levels / Higher